KEMAMPUAN MENULIS PANTUN SISWA KELAS VII SMP - Sri Nurul Azmi; Fahruddin Hanafi; Aris Badara (PT. CASA CENDEKIA MEDIA, 2025)
The purpose of this study was to describe the ability to write pantun of class VII students of SMP Negeri 5 Kendari. This study is classified as a field research. The method used in this study is descriptive quantitative. The population in this study were all class VII students of SMP Negeri 5 Kendari totaling 442 people. The number of samples in this study was 168 people. The data collection technique used in this study was a pantun writing test given to students. Based on the results of thestudy and data analysis carried out, data from 168 students of class VII of SMP Negeri 5 Kendari who were respondents, as many as 138 (82.14%) were categorized as capable of writing pantun and 30 students (17.85%) were categorized as not yet capable of writing pantun. Classically, the ability to write pantun of class VII students of SMP Negeri 5 Kendari is categorized as not yet capable because the percentage of student ability only reaches 82.14%, still below the classical completeness standard of 85%. The ability to write pantun covering the theme aspect is 79.16%, structure 89.28%, rhyme 73.21%, rhyme and content of pantun 81.54%, and message and mandate 69.64%. Of the 5 aspects assessed, only 1aspect is categorized as classically capable, namely the structure aspect.